Updating the genomic and clinicopathologic features of thoracic SMARCA4-deficient undifferentiated tumor: a mini-series including a long-term survivor - Ofori, Kenneth; Pagan, Carlos; Smithgall, Marie C.; Jadalla, Asma Salah; Upadhyay Baskota, Swikrity; Crapanzano, John P.; Hsiao, Susan; Mansukhani, Mahesh M. (Frontiers in Oncology, 2025)
IntroductionThoracic SMARCA4-deficient undifferentiated tumor (SMARCA4-dUT) is a recently described type of lung cancer, presenting as a bulky mass variably involving the mediastinum and the lung in patients with smoking history, and exhibits adverse prognosis. The essential diagnostic immunomorphologic features and typical genomic findings have been described. However, there is a continuing need to catalogue the spectrum of genomic changes underlying the disease, the heterogeneity of antigen expression in order to avoid diagnostic pitfalls, and any variability in patient outcomes. We sought to update the literature on the clinicopathologic and genomic characteristics of thoracic SMARCA4- dUT.MethodsWe searched for cases diagnosed in our institution, reviewed clinical data, performed comprehensive genomic analysis, and evaluated immunomorphologic features.ResultsFour cases (three males and one female) were identified at a median age of 61.5 years (range, 49–72 years), all with smoking history. The series included a patient with limited disease treated with surgery and adjuvant chemotherapy, who remained disease-free over a year after diagnosis, underscoring the importance of lung cancer screening among smokers and the possibility of a subgroup of thoracic SMARCA4-dUT with less aggressive disease. In addition to the known immunophenotypic features of the disease, we identified the expression of FLI (in three out of three cases) and WT-1 (in one of three cases), which are endothelial and mesothelial markers, and are findings to be cognizant of to avoid misdiagnosis as angiosarcoma or mesothelioma, respectively. While the neuroendocrine markers synaptophysin and CD56 were variably expressed in some cases, the expression of INSM1 was absent in all cases. Genomic analysis demonstrated tobacco-related features, including a high median tumor mutation burden and TP53 variants. In this limited series, mutational signature analysis revealed evidence of SBS87 as the predominant single-base substitution COSMIC signature.ConclusionOur work expands the possible diagnostic antigen expression of thoracic SMARCA4-dUT, contributes to the emerging reports on patients with variant disease presentation, and highlights the need for large-scale genomic studies to determine additional mechanisms of the initiation of carcinogenesis.